Pakistan Journal of Library and Information Science: A bibliometric analysis - Nosheen Fatima Warriach (Pakistan Journal of Information Management & Libraries, 2016)
Pakistan Journal of Library and Information Science (PJLIS) is an HEC recognized journal published by the Department of Library and Information Science, University of the Punjab, Lahore. A total of 111 publications from 11 issues of PJLIS were published during 1995 to 2010. It has outstanding contribution in the dissemination of LIS research on national and international level as it publishes both in print and electronic format. A bibliometric analysis of contributions published in the PJLIS from 1995 to 2010 has been presented in this paper. Attempt has been made to study all 11 issues of this journal on the basis of different parameters, viz., author productivity, extent of authors' collaboration, authors' institutional affiliation, authors' geographic affiliation, type of publication, language of papers, number of citations used per article, length of papers, and year-wise distribution of papers.